PELATIHAN PEMBUATAN BONEKA JARI AGAMA (BONJARMA) BAGI GURU RA ATH-THOORIQ SINGARAJA SEBAGAI UPAYA MENANAMKAN KARAKTER TOLERANSI BERAGAMA PADA ANAK USIA DINI - Setyowahyudi, Rendy; Sari, Ni Made Dainivitri Sinta; Paramita, Made Vina Arie; Imamah, Nur; Indana, Nurul (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
The issue of religious tolerance is currently being hotly discussed. Even the Ministry of Education, Culture, Research and Technology has listed it as one of the three major sins of education. The problem of religious tolerance is also felt at the PAUD level, including at RA Ath-Thooriq Singaraja. So far, teachers have had difficulty choosing the right way to teach religious tolerance to early childhood there. The purpose of this community service activity is to provide knowledge and skills to RA Ath-Thooriq Singaraja teachers in making religious finger puppets as an effort to instill a character of religious tolerance in early childhood. The method used in this community service activity is to hold training activities for 12 RA Ath-Thooriq Singaraja teachers. Data from the results of the activity were collected using interviews, observations and documentation in the form of photos of the activity. The results obtained were increased knowledge and skills of teachers in making religious finger puppets after this community service activity was carried out.